Can children create mind maps as planning tools for writing? - Cockburn, Elaine (2011)
This thesis reports an investigation into primary-aged children's ability to learn how to construct mind maps and use these as a tool to support thinking and planning for written tasks. Little research has investigated the kinds of mind map produced by 7-11 year old children, or the impact on an associated written task. It is argued therefore that a closer examination of these claims might shed light on how children learn and use such representations.